Comparative Analyses of Rhizosphere Bacteria Along an Elevational Gradient of Thuja sutchuenensis - Zuo, You-wei; Zhang, Jia-hui; Ning, Deng-hao; Zeng, Yu-lian; Li, Wen-qiao; Xia, Chang-ying; Zhang, Huan; Deng, Hong-ping (Frontiers in Microbiology, 2022)
Thuja sutchuenensis Franch. is an endangered species in southwestern China, primarily distributed in 800-2100 meters of inaccessible mountainous areas. Rhizosphere soil physicochemical properties and bacterial communities play an essential role in managing plant growth and survival. Nonetheless, the study investigating rhizosphere soil properties and bacterial community diversity of T. sutchuenensis is limited. The present study investigated soil properties, including soil pH, organic matter, water content, nitrogen, phosphorus, and potassium contents, and bacterial communities in nearly all extant T. sutchuenensis populations at five elevational gradients. Our results demonstrated that elevational gradient decreased rhizosphere and non-rhizosphere soil phosphorus content but increased potassium content. In addition, elevational gradient was the dominant driver for the diversity differentiation of soil bacterial community. Proteobacteria and Acidobacteria were the dominant bacterial phyla distributed in the rhizosphere and non-rhizosphere soils. Co-occurrence network analysis identified key genera, including Bradyrhizobium, Acidicapsa, Catenulispora, and Singulisphaera, that displayed densely connected interactions with many genera in the rhizosphere soil. The dominant functions of the rhizosphere bacteria included ABC transporters, butanoate metabolism, and methane metabolism. Further correlation analysis found that soil phosphorus and potassium were the dominant drivers for the diversity of soil bacteria, and Planctomycetes, especially Blastopirellula, Planctomycetes, and Singulisphaera, contributed significantly to the two soil nutrients. Our findings demonstrated that elevational gradient was the primary driving factor for the diversity differentiation of soil bacterial community. In addition, the study identified that many bacteria genus might play a critical role in nutrient cycling of T. sutchuenensis. This comprehensive study generated multi-dimensional perspectives for understanding the soil bacterial community structures of T. sutchuenensis, and provided valuable findings for species conservation at large-scale perspectives.